Interpreting Ecclesiastes: Readers Old and New : Readers Old and New - Dell, Katharine J. (Katharine Julia), 1961- (Book collections on Project MUSE., 2013)
Readers of texts come from all generations, from different contexts and with different agendas. This book gives a sample of what both ancient and contemporary readers have brought to the book of Ecclesiastes in the quest for illumination of the text and for their own enlightenment, often furnishing their own agenda. Debates over meaning are formed, shaped, and illuminated by the interpreters themselves. Part One looks at ancient interpreters and at their methods of approaching the text. Jewish and Christian interpreters alike sought to find meaning amongst some of the key puzzles of the book: why does the author call himself 'the son of David' and appear to be Solomon when his pen name also seems to be Qoheleth? Why the contradictions in content? How did such an unorthodox book come to be canonized? How did the dualistic contemptus mundi interpretation of the vanity theme perpetuated by Jerome and others come to hold the field for so long? And how did Luther and the reformers seek to rectify that approach? These questions and others are addressed in this book, looking through the lens of past interpretation. Part Two acknowledges our increasing self-awareness of the importance of method in approaching biblical texts and turns to a sample of modern interpretations from familiar reading groups such as the ecologist, the animal theologian, the liberationist, the post-colonialist, and the feminist. It will be seen that different modern approaches often enlighten the interpretation of specific verses within Ecclesiastes and hence that no one method is a wholesale 'solution' to interpretive concerns. -- Publisher.